THE CONDITIONS OF TSS AND TDS VALUES IN THE TOXICITY TEST OF PALM OIL LIQUID WASTE AGAINST THE SURVIVAL OF BAUNG FISH (Hemibagrus nemurus) - Husna, Hidayatul; Hasibuan, Saberina; Syafriadiman, Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis research was conducted on November-December 2018 in the Laboratory of Environmental Quality of Culture Fisheries and Marine Riau University. Objective of this study to determine the conditions of TSS and TDS value in the toxicity test treatment  aet and survival rate’s Baung fish. Method this research  used experiment  with completely randomized design (CRD) and 3 replications. LC50 96 hour value determine by using EPA Probit analysis with software of SPSS Program. Result of acute toxicity test that the LC50 96 hour and biological safety level (BSL) value were 230,57 ml/L and 2,30 ml/L. TSS and TDS values were obtained 85,71 ml/L and 2,30 ml/L. then, absolute weight growth, specific growth rate, and survival growth rate values of Baung fish were 2,39 g, 3,42% and 93% respective. Water quality parameters such as temperature range from 26-28 0C, pH ranges from 5,6-8,0, DO ranges from 4,1-2,3 mg/L, CO2 ranges from 8,60-13,50 mg/L and amonia ranges from 0,018-0,056 mg/L. Keywords: toxicity, sub lethal, TSS, TDS Hemibagrus nemurus